209k views
5 votes
-2(3x+4) - x+6 = -5x -2 (x+1) +5

User FatBruno
by
5.2k points

2 Answers

3 votes

Answer:

There are no solutions

Explanation:

−2(3x+4)−x+6=−5x−2(x+1)+5

(−2)(3x)+(−2)(4)+−x+6=−5x+(−2)(x)+(−2)(1)+5(Distribute)

−6x+−8+−x+6=−5x+−2x+−2+5

(−6x+−x)+(−8+6)=(−5x+−2x)+(−2+5)(Combine Like Terms)

−7x+−2=−7x+3

−7x−2=−7x+3

Step 2: Add 7x to both sides.

−7x−2+7x=−7x+3+7x

−2=3

Step 3: Add 2 to both sides.

−2+2=3+2

0=5

Answer - There are no solutions

User Emil Rehhnberg
by
5.6k points
4 votes

Answer: no value

Explanation:

Step by step explanation is attached

-2(3x+4) - x+6 = -5x -2 (x+1) +5-example-1
User FinalDark
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.